2017
DOI: 10.1111/ivb.12187
|View full text |Cite
|
Sign up to set email alerts
|

Elemental characterization of the exoskeleton in the whipscorpions Mastigoproctus giganteus and Typopeltis dalyi (Arachnida: Thelyphonida)

Abstract: The arthropod cuticle is a structurally diverse secretion that is largely composed of lipids, proteins, and α‐chitin that function together in protection, prey capture, and as a skeletal framework for efficient and diverse means of locomotion. Aquatic, aerial, and terrestrial arthropods are well known to enrich their cuticles with trace elements that are proposed to strengthen or otherwise enhance specific regions of the exoskeleton. In this study, we provide evidence that whipscorpions (vinegaroons) enrich th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Although at least part of the Al may be a contamination from the aluminum scanning electron microscope stubs, herein we provided the first evidence for the presence of the post-transition metal Al in tick exoskeleton. As found here in ticks, the presence of certain elements such as Si is rare in arthropod exoskeleton [6] .…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Although at least part of the Al may be a contamination from the aluminum scanning electron microscope stubs, herein we provided the first evidence for the presence of the post-transition metal Al in tick exoskeleton. As found here in ticks, the presence of certain elements such as Si is rare in arthropod exoskeleton [6] .…”
Section: Resultssupporting
confidence: 67%
“…The exoskeleton is a structure that protects arthropods from natural threats such as predators and diseases. In ticks as in other terrestrial arthropods, the relative amount of chitin fibrils and protein matrix, protein composition, pH/water content of the matrix, composition of chemical elements and cross-linking of the matrix protein affect the properties of the exoskeleton [3] , [4] , [5] , [6] , [7] . It has been shown that mechanical properties of tick cuticle change during tick feeding to support the increase in body size and mass during this process [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of NADPH in ticks have been associated with response to Anaplasma phagocytophilum pathogen infection and tolerance to oxidative stress [61,62]. The source of other chemical elements such as Na, K, Cl, and P, which may contribute to cement biomineralization and coating [29,63] probably come from environmental sources (e.g., water, air, and soil).…”
Section: Physical and Chemical Properties Of Tick Salivary Glands Andmentioning
confidence: 99%
“…In ticks, as in other terrestrial arthropods, the relative amount of chitin fibrils and protein matrix, protein composition, pH/water content of the matrix, composition of chemical elements, and cross-linking of the matrix protein affect the properties of the exoskeleton (Cribb et al, 2010;Flynn and Kaufman, 2015;Gallant et al, 2016;Gallant and Hochberg, 2017;Suppan et al, 2018). It has been shown that mechanical properties of tick cuticle change during tick feeding to support the increase in body size and mass during this process (Flynn and Kaufman, 2015).…”
Section: Introductionmentioning
confidence: 99%